Ecological methods in forest pest management - Wainhouse, David (Oxford biology readers., 2005)
Throughout the world there is a need to control forest insect pests. This text focuses predominantly on insect pests, but many examples relate to fungal pathogens, some of which are vectored by forest insects. It looks at the development of Integrated Pest Management (IPM).